Application and Prospect of New Steel Corrugated Plate Technology in Infrastructure Fields. Issue 1 (January 2020) - Wang, Xingping; Wang, Zhijie; Guo, Chun; Han, Yu; Zhao, Jianhua; Lu, Nan; Tang, Huizhi
Abstract: This paper systematically analyses the application status and advantages of steel corrugated plate and it's composite structure technology in domestic and foreign infrastructure construction, such as in the tunnel fields. From the aspects of Engineering characteristics, environment and energy saving, etc. We put forward the research ideas, development prospects and application ideas of steel corrugated plate technology in the field of infrastructure.